Kajian kekonduksian ionik terhadap adunan elektrolit polimer PVC-getah asli terepoksi dan PVdF-getah asli terepoksi - Chee, Lip Chew (2005)
This research is focusing on the development of new thin film electrolytes based on poly (vinly chloride) (PVC)/epoxidised natural rubber (ENR-50) blends and poly (vinylidene fluoride) (PVdF)/epoxidised natural rubber (ENR-50) blends by solvent casting method. Lithium triflate (LiCF3SO3) and lithium imides (LiN(CF3SO3)2) were used as doping salt to provide ion for ionic conduction. Plasticizers such as ethylene carbonate (EC) and propylene carbonate (PC) are used to enhance the conductivity of the film polymer electrolyte. In this study the ionic conductivity, morphology, FTIR spectroscopy and thermal properties have been determined for both unplasticized and plasticized polymer electrolyte systems. The electrical conductivity of all samples were calculated using the bulk resistance values obtained from the complex impedance plot in the frequency range between 1 Hz to 1 MHz. Without any plasticizer, the PVC/ENR- 50/LiCF3SO3 and PVC/ENR-50/LiN(CF3SO3)2 blend polymer electrolyte systems have ionic conductivities in the range 10-11 to 10-8 S/cm at ambient temperature. Meanwhile, the PVdF/ENR-50/LiCF3SO3 and PVdF/ENR-50/LiN(CF3SO3)2 blend polymer electrolyte systems exhibit ionic conductivities in the range 10-8 to 10-5 S/cm. Incorporating 100% of EC/PC by weight fraction of polymer to the polymer electrolyte systems PVC/ENR-50/LiCF3SO3 and PVC/ENR- 50/LiN(CF3SO3)2 have ionic conductivity in the range 10-10 to 10-6 S/cm at ambient temperature. The PVdF/ENR-50/LiCF3SO3 and PVdF/ENR- 50/LiN(CF3SO3)2 plasticizer blend polymer electrolyte system exhibit ionic conductivities in the range 10-6 to 10-5 S/cm. PVdF/ENR-50/LiCF3SO3/EC/PC and PVdF/ENR-50/LiN(CF3SO3)2/EC/PC gel blend polymer electrolyte systems exhibit ionic conductivities in the range 10-4 to 10-3 S/cm at ambient temperature.